Produksi Tepung Ikan Rucah Untuk Peningkatan Pendapatan Nelayan di Paciran Lamongan - Choirul Anam; Cahyo Indarto (Universitas Muhammadiyah Surabaya, 2018)
The purpose of community service is to provide samples and training to fishermen about protein production technology of protein-rich fish protein from trash fish that is useful to increase fishermen's income. The methods used are lectures, discussions, demonstrations or training, mentoring and assignment and business feasibility analysis. Characteristics of members of harmonious fishermen most of the age between 17 years to 47 years, educated Junior High School / MTs and High School / MA. Experience as a fisherman between 5 to 20 years. Needs of raw materials trash fish as much as 10 kg with price Rp 27.000 and produce flour of 8 Kg with sale price Rp 7.000 per Kg. Gross income of Rp 56,000, - and profit of Rp 29,000. Comparison between profit and expenses, ie Rp. 29.000,00: Rp. 27.000,00 = 1,1 (B / C). So fish meal business is quite feasible to be developed and can increase fisherman income about 107 percent.